Paris Peace Conference and beyond, 1919-1939. - Cecil of Chelwood, Robert Gascoyne-Cecil, Viscount, 1864-1958; Balfour, Arthur James, 1848-1930; Great Britain. Foreign Office; National Archives (Great Britain); British Library (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2019)
The Paris Peace Conference was a meeting of Allied diplomats that took place in the aftermath of the First World War. Its purpose was to impose peace terms on the vanquished Central Powers and establish a new international order. This collection contains archival material relating to this tumultuous period in European and world history. The documents cover the treaties of Versailles, Saint-Germain-en-Laye, Neuilly-sur-Seine, Trianon, Sèvres, Lausanne, and Locarno, as well as the foundation of the League of Nations. Together, these treaties severely curtailed German power and influence, redrew national boundaries in Europe and the Middle East, and led to the dissolution of the Ottoman Empire.
Date range: 1919-1939.
Keywords: Europe -- Politics and government -- 1918-1945.; World politics -- 1919-1932.; World War, 1914-1918 -- Treaties; Treaty of Versailles -- (1919 June 28); League of Nations